Analisis Perencanaan Strategis Sumber Daya Dosen di STKIP Yayasan Abdi Pendidikan - Mures Walef, Sri; Poni Ernis; Sufia Retti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the performance measurement of lecturers at STKIP Yayasan Abdi Pendidikan in the fields of teaching, research, and community service. The method used is a qualitative approach through observation, interviews, and documentation studies. The results of the study indicate that although lecturers have carried out tridharma activities according to their workload, there are still shortcomings in performance measurement, especially in terms of data validity and the inconsistency of research or community service with the scientific field. In addition, there are no performance indicators that explicitly support the achievement of the institution's vision and mission. By using the Guidance Scorecard, the relationship between lecturer performance indicators and the institution's strategic goals is analyzed, which shows the importance of strengthening the lecturer performance evaluation system based on relevant indicators and integrated with the institution's strategic direction. Keywords: Lecturer Performance, Guidance Scorecard, Performance Measurement